Effects of Age and Task Load on Drivers’ Response Accuracy and Reaction Time When Responding to Traffic Lights - Salvia, Emilie; Petit, Claire; Champely, Stéphane; Chomette, René; Di Rienzo, Franck; Collet, Christian (Frontiers in Aging Neuroscience, 2016)
Due to population aging, elderly drivers nowadays represent a significant rate of car drivers. Yet, we do not know exactly how aging may alter sensorimotor functions and therefore, its actual impact on safety. This paper aimed to assess to which extent elderly drivers are sensitive to various task loads and how this could impact reaction time with application to driving. Old and middle-aged people completed reaction time tasks (RT) close to those drivers usually have to manage while driving. We requested the participants to detect and respond to traffic lights or a traffic light arrows as quickly as possible during three experimental conditions of increasing difficulty. We expected that decision-making should be impacted through RT by manipulating the number of cues to be processed in both groups. The first test was a simple RT-task. The second and third tests were choice reaction time tasks requiring the processing of three or five information respectively. Responses had to occur within a 2s time-window, otherwise the result was considered a no-response. We showed that RT, error rate and no-response rate increased as a function of task difficulty, in both groups. However, the middle-aged people group outperformed the elderly group. RT difference between the two groups increased drastically with task difficulty. In the third test, the rate of no-response suggested that old drivers need more than 2s to process complex information and respond accurately. Both prolonged RT and no-response rate, especially for difficult tasks, may attest impairment of cognitive abilities, related to aging. Therefore, usual driving conditions for young drivers could be complex and stressful for the elderly who should thus be informed about the effects of normal aging upon driving with simple recommendations and advices.